2016
DOI: 10.1002/app.43396
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and dynamical mechanical properties of poly ether ketone ketone (PEKK) with meta phenyl links

Abstract: Poly ether ketone ketone (PEKK) with different proportion of meta phenyl links were investigated by combining differential scanning calorimetry and dynamic mechanical analysis. The influence of the Terephthalyl/Isophthalyl isomers (T/I) ratio on the vitreous phase is mild, the shift of the glass transition is limited to a few degrees and the vitreous G′ is only sensitive to the content of the crystalline phase. Contrarily, the increase of meta isomers is responsible for a significant decrease of the melting te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 48 publications
(69 reference statements)
4
42
0
Order By: Relevance
“…We observed that w 1 is closed to 1 for low temperatures and then decreases to values lower than 0.5 for temperatures above 260 C. This shows that the formation of the secondary crystallization is promoted for low degree of supercooling. This observation has also been reported by few authors [18,39] with the increase of a first endothermic peak which occurs 10 C above the annealing temperature attributed to the melting of the secondary crystallization. In fact, for high annealing temperatures, the diffusion process is very important with a high mobility of the chains allowing the enhancement of the crystalline phase by the growth of a second crystalline structure within lamellae.…”
Section: Isothermal Crystallization Kinetic Modelingsupporting
confidence: 67%
See 3 more Smart Citations
“…We observed that w 1 is closed to 1 for low temperatures and then decreases to values lower than 0.5 for temperatures above 260 C. This shows that the formation of the secondary crystallization is promoted for low degree of supercooling. This observation has also been reported by few authors [18,39] with the increase of a first endothermic peak which occurs 10 C above the annealing temperature attributed to the melting of the secondary crystallization. In fact, for high annealing temperatures, the diffusion process is very important with a high mobility of the chains allowing the enhancement of the crystalline phase by the growth of a second crystalline structure within lamellae.…”
Section: Isothermal Crystallization Kinetic Modelingsupporting
confidence: 67%
“…This is due to a lowering of the macromolecular chains regularity with the T/I ratio which decreases the crystalline phase compactness [9]. PEKK 60/40 has a T g about 156 C and a T m about 300 C [18], which is lower than the one for PEEK (around 340 C [2]). This is quite interesting for processing regarding part manufacturing costs and possible degradation at high temperature.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…reported the evolution of melting and crystallization behavior of PEKK upon the influence in meta links content. We recently published a combined study by differential scanning calorimetry and dynamic mechanical analysis (DMA) in the solid state of PEKK with different thermal history and T / I ratio (80/20, 70/30, 60/40) . In the vitreous state, very few works concern sub‐glass relaxations of PEKK.…”
Section: Introductionmentioning
confidence: 99%